2016
DOI: 10.1242/dev.140046
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule that disrupts a key event during the oocyte-to-embryo transition in C. elegans

Abstract: The complex cellular events that occur in response to fertilization are essential for mediating the oocyte-to-embryo transition. Here, we describe a comprehensive small-molecule screen focused on identifying compounds that affect early embryonic events in Caenorhabditis elegans. We identify a single novel compound that disrupts early embryogenesis with remarkable stage and species specificity. The compound, named C22, primarily impairs eggshell integrity, leading to osmotic sensitivity and embryonic lethality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…As above, supplemental cholesterol is necessary in our system. Perhaps related, we have found that the compound C22, which produces 100% sterility in standard agar plates, 53 has more variable effects in our corral system.…”
Section: Discussionmentioning
confidence: 64%
“…As above, supplemental cholesterol is necessary in our system. Perhaps related, we have found that the compound C22, which produces 100% sterility in standard agar plates, 53 has more variable effects in our corral system.…”
Section: Discussionmentioning
confidence: 64%
“…Comparisons between the embryonic lethality caused by ZTDO and another embryocide reveal key differences in mode of action. In C. elegans, C22 is a potent and species-specific embryocide that disrupts the oocyte-to-embryo transition in the maternal environment (Weicksel et al, 2016). C22 acts only through the parental hermaphrodites and targets oocytes just prior to fertilization, but has no effect on any other developmental stages, such as embryos, larvae and adults.…”
Section: Discussionmentioning
confidence: 99%
“…CREB3 has been identified in regulating Golgi-stress and activation of ARF4 (Reiling et al 2013). A previous study in C. elegans links let-607 with the upregulation of sec-23 and other proteins involved in secretion (Weicksel et al 2016).…”
Section: Immunity Response Network Regulates Lipid Bilayer Stressmentioning
confidence: 98%